AGEING WITH SMARTPHONES ‘FROM BELOW’: INSIGHTS FROM JAPAN, UGANDA, AL-QUDS AND IRELAND - de Vries Kedem, Maya; Haapio-Kirk, Laura; Hawkins, Charlotte; Miller, Daniel (AoIR Selected Papers of Internet Research, 2020)
AGEING WITH SMARTPHONES ‘FROM BELOW’: INSIGHTS FROM JAPAN, UGANDA, AL-QUDS AND IRELAND This session examines new ways to theorize the smartphone, based on a comparative study of smartphone use amongst older people in four different fieldsites for a period of 16 months ethnographic fieldwork. Along with gender, age is one of the primary parameters by which societies throughout history have structured and governed themselves (Spencer, 1990). Since the 1960s, however, we have lived with an unprecedented modern consciousness that has presented an increasingly powerful challenge to this hegemonic principle by placing a high value on youth culture (Hodkinson, 1999). As a result, there is a new uncertainty about the meaning of age (Degnen, 2007). In addition, age has also extended class discrepancies, as those around the world between the ages of 45–70 have become a class that has settled its children and can now capitalize upon the new choices of consumer culture (Blaikie, 1999). Yet, these ageing populations increasingly face problems of loneliness linked to a loss of authority of seniority (Hazan, 1994), though this may be alleviated by contact through digital devices and networked platforms, mainly smartphones. Focusing on populations in their sixties, seventies and eighties is one of the panel’s major contributions, as mostly up until now smartphones have been associated with the idea of a youth technology and many of their attributes associated with that age group (Jenkins et al., 2016). Hence, we wish to release the smartphone from its earlier connections, allowing us to theorise it more broadly as part of the life of ‘non-digital natives’. The four papers in the panel show how understanding smartphones is more than simply addressing the culture of ‘apps’ or the ‘culture of connectivity’. Rather, the smartphone presents an ecology of digitization tailored to the specific configurations of the individual user which is best understood through the ethnographic method of holistic contextualization. This approach links smartphone usage with all aspects of offline life and creates a role for digital anthropologists who are well placed to tackle fundamental questions about smartphones because they can gain access to this intimate and mainly private configuration and processes of personalization within their social and cultural contexts. Using Pype’s (2019) concept of `smart from below’ we provide illustrations showing how it is the users who actually create smartphones. To follow normative contemporary theory, this would require situating our findings in relation to established theoretical debates about new communications media. The nuance given by comparing four fieldsites with a vast variety of smartphone usage ties us to the initial context of difference and comparison, thus providing novel conceptualizations of the smartphone. These include concepts such as ‘screen ecology’, ‘the transportal home’, ‘beyond anthropomorphism’, ‘social ecology’, ‘perpetual opportunism’, ‘contradiction and ambivalence’, ‘the control hub’, ‘multifaceted connectivity’ and others. Each of these may help us to visualise, understand, and explain what people do with their smartphones and why. But where this subsumes Uganda, al-Quds, alongside Japan and Ireland there is a danger of creating neo-imperial homogenisations based on citing de-contextualised critiques. Our panel strives to describes an alternative path that could allow for theoretical development of the contemporary smartphone, while avoiding these betrayals of either substance or original insight. Three papers provide more extended examples of what we have achieved ‘the transportal home’ through fieldwork in Japan, ‘care transcending distance’ through fieldwork in Uganda, and we explore ‘contradiction, ambivalence and multifaceted connectivity’ though fieldwork in al-Quds. The fourth paper is more theoretical, aiming to link between the presented ethnographies and exemplify the grounding of theory of the smartphone. We hope that our panel will encourage global discussion of the role of the smartphones in the everyday lives of individuals from all age groups, not just the young. Such an expansion would allow for a deeper understanding of this device which, as we demonstrate, is so central to many people’s experience of social life, home, and care. References Blaikie, A. (1999). Ageing and popular culture. Cambridge University Press. Degnen, C. (2007). Minding the gap: The construction of old age and oldness amongst peers. Journal of Aging Studies, 21(1), 69-80.‏ Hazan, H., & Ḥazzān, Ḥ. (1994). Old age: Constructions and deconstructions. Cambridge University Press. Hodkinson, P., & Bennett, A. (Eds.). (2013). Ageing and youth cultures: Music, style and identity. A&C Black.‏ Jenkins, H., Shresthova, S., Gamber-Thompson, L., Kligler-Vilenchik, N., & Zimmerman, A. (2018). By any media necessary: The new youth activism (Vol. 3). NYU Press. Pype, K. (2017). Smartness from below: variations on technology and creativity in contemporary Kinshasa. What Do Science, Technology, and Innovation Mean from Africa, 97-115. Spencer, P. (1990). Anthropology and the Riddle of the Sphinx: Paradoxes of Change in the Life Course. Routledge.‏